Database Management Systems - Ramakrishnan, Raghu; Gehrke, Johannes (McGraw-Hill Higher Education, 2003)
Database Management Systems has quickly become one of the leading texts for database courses, known for its practical emphasis and comprehensive coverage. The third edition features new material on database application development, with a focus on Internet applications. The hands-on approach introduces students to current standards, including JDBC, XML, and 3-tier application architectures. A new, flexible organization allows instructors to teach either an applications-oriented course or an introductory systems-oriented course. The revised “part” organization with (new) Overview chapters makes it easy to select the chapters you need; in-depth chapters within each part can be optional. This very current new edition also features pedagogical improvements (e.g., chapter objectives, review questions), and updated and extended discussions of data mining, database tuning wizards, decision support, information retrieval, Internet security, object-oriented databases, transaction processing, and XML data management. Throughout, the coverage has been revised and expanded to reflect the new SQL:1999 standard, including extensions that support multimedia data, object-relational databases, OLAP, recursive queries, spatial data, and SQL-J. The flexible organization and up-to-date discussion of advanced topics also makes the book ideal for use in a two-course sequence. More about the book's organization. Online material Supporting material for the Third Edition Supporting material for the Second Edition (Published August 1999 to July 2002) Supporting material for the First Edition (Published August 1996 to July 1999) If you have further questions, contact Raghu Ramakrishnan at Wisconsin or Johannes Gehrke at Cornell. If you are an instructor, you can request a FREE SAMPLE COPY. If you are using the book and have found bugs or typos, or want to comment on the presentation or content, please send email.